Application of a novel diol-based porous organic polymer to the determination of trace-level tetracyclines in water. Issue 18 (26th April 2019) - Cui, Changzheng; Cao, Zan; Zhang, Shenping; Hu, Yaru; Jiang, Lei; Yao, Shijie; Ye, Hui; Zhou, Yanbo; Hu, Jun; Lin, Kuangfei; Zhang, Tian-Yang
Abstract : A novel diol-based porous organic polymer (NTdiol-POP) was used as a new solid phase extraction material to improve extraction efficiency of trace tetracyclines in water before HPLC-MS/MS analysis. Abstract : The solid phase extraction (SPE) method is often used to enrich trace antibiotics in water before analysis by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), but the improvement of extraction efficiency has always been the hot issue in this method, which may be realized by developing new SPE materials and optimizing extraction conditions. Tetracyclines (TCs) are a class of common antibiotics, but appropriate SPE materials specifically used to detect them are lacking. Common SPE materials show low and unstable recoveries during the extraction and detection of TCs. In this study, a novel diol-based porous organic polymer (NTdiol-POP) was used as a new SPE material to detect trace TCs in water. This material has specific adsorptive properties for TCs via hydrogen bonds, electrostatic attractive interactions, and π–π interactions. The results show that the NTdiol-POP cartridges have higher recoveries (83.3–118.1%) for determining TCs than common SPE cartridges. Under optimum SPE conditions using NTdiol-POP, TCs were adsorbed at pH 5.0 and eluted with a solution of formic acid/methanol (7%/93%, v/v). Meanwhile, chromatographic separation conditions and MS/MS parameters in multiple reaction monitoring (MRM) mode were optimized to improve the sensitivity and specificity of the instrumental analysis. The limit of detection varied from 0.078 to 2.18 ng L −1, while the limit of quantification varied from 0.26 to 7.25 ng L −1 . An assessment of the matrix effects in drinking water exhibited a slight signal variation for most TCs (−8.4% to 2.5%) except oxytetracycline, for which the detection signals were enhanced by 27.0%. The proposed method was successfully applied to determine the trace TCs in three reservoirs of East China.